2007
DOI: 10.1111/j.1462-2920.2006.01215.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection, diversity and expression of aerobic bacterial arsenite oxidase genes

Abstract: The arsenic (As) drinking water crisis in south and south-east Asia has stimulated intense study of the microbial processes controlling the redox cycling of As in soil-water systems. Microbial oxidation of arsenite is a critical link in the global As cycle, and phylogenetically diverse arsenite-oxidizing microorganisms have been isolated from various aquatic and soil environments. However, despite progress characterizing the metabolism of As in various pure cultures, no functional gene approaches have been dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
161
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(165 citation statements)
references
References 43 publications
4
161
0
Order By: Relevance
“…The major groups of As oxidizing bacteria were α-Proteobacteria and β-Proteobacteria in the rhizosphere and were mainly rhizospheric microbes ( Figure S3, Supporting Information), while undefined cluster 1 and cluster 7 was enhanced on roots ( Figure S3, Supporting Information). The diversity of the aroA-like gene revealed in this study is similar to what has been observed in many other diverse environments, such as mining-impacted soils and As-contaminated lake sediments; 18,43,44 whereas in geothermal environments, aroA-like microbes were dominated by Aquificae. 18,45 Arsenic oxidation and reduction (ArsC) share some microbial groups, such as Bradyrhizobiaceae and Rhizobiaceae, and also some different groups ( Figures S1 and S3, Supporting Information).…”
Section: ■ Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The major groups of As oxidizing bacteria were α-Proteobacteria and β-Proteobacteria in the rhizosphere and were mainly rhizospheric microbes ( Figure S3, Supporting Information), while undefined cluster 1 and cluster 7 was enhanced on roots ( Figure S3, Supporting Information). The diversity of the aroA-like gene revealed in this study is similar to what has been observed in many other diverse environments, such as mining-impacted soils and As-contaminated lake sediments; 18,43,44 whereas in geothermal environments, aroA-like microbes were dominated by Aquificae. 18,45 Arsenic oxidation and reduction (ArsC) share some microbial groups, such as Bradyrhizobiaceae and Rhizobiaceae, and also some different groups ( Figures S1 and S3, Supporting Information).…”
Section: ■ Discussionsupporting
confidence: 86%
“…16,17 On the other hand, some heterotrophic as well as chemoautotrophic microorganisms are able to oxidize As(III) to As(V). 18 Arsenite oxidation is suggested to facilitate As sequestration in metal oxides and is often used as a tool to remediate As-contaminated waters and soils. 19 Arsenic-reducing and arsenic-oxidizing microbes often coexist in the environment, and their relative abundance and activity determine the geochemistry and fate of As in the environment.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The mixture contained 5 μL 10 × PCR buffer, 4 μL dNTP (1.5 mmol/L, final concentration), 1 μL of each primer (0.4 mmol/L, final concentration), 0.2 μL BSA (10 mg/mL), 2 μL template DNA, 0.4 μL Taq DNA polymerase (5 U/μL, Takara, China) and addition of RNase free ddH 2 O (Takara, China) to a final volume of 50 μL. Universal eubacterial primers (27F:5′-AGAGTTTGATCCTGGCTCAG-3′;1492R:5′-GGYT ACCTTGTTACGACTT-3′) (Lane, 1991) targeting 16S rRNA gene and primers (F:5′-GTSGGBTGYGGMTAYCABGYCTA-3′; R:5′-TTG TASGCBGGNCGRTTRTGRAT-3′) targeting aroA gene (Inskeep et al, 2007) were used for PCR. The occurrence of arsenate reductase gene arsC in the isolated strain was investigated using five reported primers (Bachate et al, 2009;Chang et al, 2008;Macur et al, 2004;Macy et al, 2000;Sun et al, 2004).…”
Section: Pcr Amplification Of 16s Rdna Aroa Gene and Arsc Genementioning
confidence: 99%
“…To date, all known aerobic arsenite oxidases exhibit a heterodimeric structure with molybdopterin (Mo-pterin) and Rieske-like subunits (Inskeep et al, 2007). The large subunit (AroA~90 kDa) of the arsenite oxidase is the first example of a new subgroup of the dimethylsulfoxide (DMSO) reductase family of molybdoenzymes (Ellis et al, 2001).…”
Section: As(iii)-oxidizing Bacteriamentioning
confidence: 99%
“…As mentioned above, dominant As on iron plaque is As(V), indicating the occurrence of As(III) oxidation in the rhizosphere, but the microbial-mediated As(III) oxidation in soil is largely unknown. Bacterial As(III) oxidase genes are phylogenetically diverse and ecologically widespread [85]. Microbial oxidation of As(III) to As(V) occur under both aerobic and anaerobic soil conditions, which significantly enhance the immobilization of As in the soils, due to the fact that As(V) can more easily co-precipitate with ferric iron or be adsorbed by ferrihydrite [86].…”
Section: Interactions Of Microorganisms With Iron Oxidesmentioning
confidence: 99%